SCAFFOLDING WRITING SKILL IN THE K-12 CURRICULUM - Labarrete, Rufo A (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This study aimed to assess the sixth grade teachers instructional scaffolding practices in writing as a macro language skill with the end view of developing a contextualized Detailed Lesson Plan (DLP). Using the descriptive qualitative research design, data were generated using open-ended survey questionnaire, and a focus group discussion. Results showed that the K-12 curricular contents for elementary writing were rather challenging to teach that is further aggravated by limited learning resources. Remediation Reinforcement Enrichment (RRE), Explicit Teaching (ET), Little Teacher Strategy, Group Work Technique and Detailed Lesson Plans (DLPs) are mainly utilized as primary scaffolds with the aid of visuals, graphic organizers, and technology-based learning tools. Though commendable, their scaffolding practices however still fell short in actualizing instructional scaffolding holistically. Thus, the need to further the elementary teachers’ knowledge on this dimension through professional advancement and similar activities.